Comparing factors influencing young generation cohorts for traditional marketplace preferences in Indonesia - Aswin Rahadi, Raden; S.A. Prabowo, Fajar; Pancawuri, Yulinda (International Journal of Engineering and Technology, 2019)
Traditional marketplace once used to be the place for communing for people in the past. However, due to modernization and preference switch, their customers nowadays have largely abandoned the marketplace. The situation is also worsening, with the reluctance of younger generations to follow their elderly habits of shopping in traditional marketplaces.This study aims to understand the motivating factors that influence the younger generation motivations for not shopping in traditional marketplace. In this qualitative study, two types of generation cohorts: baby boomers and generation Y is being extensively interview, to uncover their motivating factors. The findings of this study suggested that there are several common motivating factors that influence their reluctance to shop in traditional marketplaces.The findings from this research are useful for traditional marketplace stakeholders to improve the current decaying traditional marketplaces in Indonesia, in order to prevent the extinction of traditional marketplaces in the country.Â Â